A chemical and bio‐herbicide mixture increased exotic invaders, both targeted and non‐targeted, across a diversely invaded landscape after fire. Issue 2 (3rd April 2021) - Lazarus, Brynne E.; Germino, Matthew J.
Abstract: Questions: Invasive‐plant treatments often target a single or few species, but many landscapes are diversely invaded. Exotic annual grasses (EAGs) increase wildfires and degrade native perennial plant communities in cold‐desert rangelands, and herbicides are thus sprayed to inhibit EAG germination and establishment. We asked how EAG target and non‐target species responded to an herbicide mixture sprayed over a large, topographically diverse landscape after wildfire. We focused on how whole‐community and natural EAG‐pathogen treatment responses varied over years and physical properties of sites. Location: Sagebrush steppe of southwest Idaho, USA. Methods: We monitored plant cover and diversity in 41 pairs of plots located inside or outside areas (486 ha total) treated with a combined aerial broadcast spray of pre‐emergent herbicide (imazapic) and weed‐suppressive bacteria ( Pseudomonas fluorescens, "MB906") to target EAGs after wildfires. Results: EAG cover and exotic species richness were initially less in treated plots but increased to levels similar to or greater than those of untreated plots by the third post‐treatment year. The EAG pathogen Ustilago bullata was not directly affected by the treatment. The treatment increased exotic perennial forb cover in all plots and exotic annual forb cover in cooler/wetter plots but reduced exotic annual forb cover in warmer/drier plots. Cover of the invasive biennial grass Poa bulbosa decreased more across study years in untreated than treated plots. Among natives, the treatment reduced perennial grass cover and annual forb presence but led to marginal increases in perennial forb cover and, on soils with less gravel, increased shrub presence. Conclusions: A treatment targeting a single plant functional group did not achieve lasting success in these diversely invaded communities. Spraying alone did not release native perennials sufficiently to counteract the simultaneous release of secondary invaders and the return of target invaders. Planting or seeding may also be needed to achieve management goals. Abstract : A combined imazapic and weed‐suppressive bacteria treatment sprayed after fire to target exotic annual grasses did not achieve lasting success in the diversely invaded sagebrush steppe communities we monitored 2–3 years after treatment. Spraying did not release native perennials sufficiently to counteract the simultaneous release of secondary invaders. Taking the whole invasive community into account would likely increase restoration success.